Macro‐ and micronutrient‐release characteristics of three polymer‐coated fertilizers: Theory and measurements. Issue 1 (13th February 2013) - Adams, Curtis; Frantz, Jonathan; Bugbee, Bruce
Abstract In spite of several published studies we have an incomplete understanding of the ion‐release mechanisms and characteristics of polymer‐coated fertilizers (PCF). Here we extend current conceptual models describing release mechanisms and describe the critical effects of substrate moisture and temperature on macro‐ and micronutrient release of three PCF types: Polyon®, Nutricote®, and Osmocote®. Nutrient release was quantified at weekly intervals for up to 300 d from 5°C to 40°C in water and chemically inert sand, substrates that allowed release quantification without confounding effects of ion sorption/desorption. At least two release‐timeframe formulations of each PCF type were studied and all products had similar nutrient concentrations to allow isolation of the effect of coating technology. Contrary to several studies, our data and model indicate that there is no significant difference in nutrient‐release rates in water and a moist, solid substrate. This means that release rates determined in water can be used to model bio‐available nutrient concentrations in moist soil or soilless media where sorption/desorption properties alter concentrations after release. Across all PCF, the nutrients most affected by temperature were typically N, K, B, Cu, and Zn, while the least affected were P, Mg, and Fe. We also found consistent differences among the coating technologies. Osmocote fertilizers released faster than specified at both high and low temperatures. Nutricote had relatively steady release rates over time and a nonlinear response to temperature. Polyon released more slowly than specified but replicate samples were highly uniform.